Pengabdian Masyarakat Membangun Keteraturan Tata Ruang Desa: Pemasangan Plang Nama Dusun oleh Mahasiswa KKN UINSU di Desa Prapat Janji Kabupaten Asahan - Dinda Lestari; Athma Mahmuda; Rizky Ramadhani; Nur Fadhilah Syam (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The community service program by KKN students in Prapat Janji Village, Asahan Regency, was motivated by the lack of visual identity in the village, which hindered local orientation and administration. The main objective of this activity was to improve the spatial order of the village by installing name signs in the 11 existing hamlets. The implementation method included several stages: designing the signs, socializing with village officials and the community, dividing tasks among the team, and executing the installation directly at the designated locations. Daily evaluations were conducted to ensure the effectiveness and positive responses from the community. Findings showed that the name signs were successfully installed at strategic points, were aesthetically pleasing, and strengthened the collective identity of the residents. Challenges such as bad weather, access to materials, and distances between hamlets were overcome through teamwork and active participation from the community. The implications of this activity not only enhanced the spatial order of the village but also fostered a sense of ownership and pride among the residents, as well as facilitated access for outsiders, such as couriers and visitors to the village.